Failure analysis of a fracture tubing used in the formate annulus protection fluid. (January 2019) - Liu, Wanying; Shi, Taihe; Li, Si; Lu, Qiang; Zhang, Zhi; Feng, Shaobo; Ming, Chuanzhong; Wu, Kai
Abstract: In recent years, tubing failure often occurs in the ultra-deep oil and gas well with the complex geological condition, resulting in accidents and repairs during the service process in the well, even giant economic losses, and fatal disaster. So it is critical to analyze the failure reason of the fracture tubing by a systematic investigation for the prevention in advance. In this study, the failure cause of the tubing is addressed through a series of dialectical failure analysis methods. Results show that the chemical composition and mechanical properties (including tensile and impact properties) meet the requirements of API Spec 5CT and oilfield supplementary technical conditions. Most of the microstructure is sorbite, but some banded ferrites distribute in the fracture region, which result in reducing the comprehensive performances of the tubing. The results of XRD and EDS analysis of corrosion products and the annulus protection fluid show they contain SO4 2−, SiO4 2−, PO4 3−, Cl − and S 2−, which lead many longitudinal cracks to appear on the outer wall of the tubing. Then the formation of pits and occurrence of cracks induce an environmental sensitive cracking named stress corrosion cracking (SCC). In addition, the morphology of fracture and cracks was observed by scanning electron microscope and results show the fracture is a quasi-cleavage fracture. Highlights: A series of comprehensive failure analysis methods were applied to analyze the fracture failure tubing. The fracture reason, characteristic and mechanism of the fracture tubing were proposed. The corrosion mechanism of SCC was further analyzed and clarified combing with the grains structure for the first time. C ring test is firstly recommended as the evaluation criterion of the stress corrosion cracking. Advice for selection of annulus protection fluid and tubing, and stricter heat treatment requirement of tubing is proposed.